Self-Ordering Concept Food Ordering System in Restaurants - Calvin Alfaren; Rudy Arijanto (bit-Tech, 2021)
The self-ordering concept ordering system can assist restaurant operations in accepting orders, making it easier for customers to place orders for food they want to order through their respective tables. If the restaurant is crowded with customers, it is necessary to have a system that can replace the manual ordering position at the restaurant which is still considered less effective and efficient in ordering problems if the restaurant is busy with customers. With the self-ordering system, it can make it easier for restaurants to receive orders from customers who come to the restaurant independently. The self-ordering system that is made will be supported by min-max as a supporting method to find out the available stock of raw materials. This self-ordering system can make it easier for customers to order food, and it will be easier for restaurants to get orders from customers in a system